A Study On Human Resource Management Practices Among Malaysian Companies: Comparing MNC & Local Companies - Lee, Doreen Chwee Lian (2006)
The purpose of this research project is to study the human resource management practices in Malaysia, particularly to identify the differences in human resource practices among MNC and local companies in Malaysia.